PEMENUHAN KEBUTUHAN PSIKOLOGIS ANAK BERBASIS GENDER - Nur Azizah (Yinyang: Jurnal Studi Islam Gender dan Anak, 2017)
Parents should give various needs to their children and the fulfilment of their psychological need will form childrenâ€™s personality to be able to live their life. In addition, gender-based fulfilment of their psychological need will give proportional portion of their need and will avoid gender bias. This is necessary for parents to eliminate gender-based discrimination among their children.Psychological need is discussed based on the theories of Abraham Maslow and Mc. Celland, which states that psychological need should be met and provided by parents so that the children can develop properly. Male and female children are also protected by the Convention on the Rights of the Child approved by the General Assembly of the United Nations on Â November 20th 1989 and the role of parents and families is reflected in the Law of the Republic of Indonesia Number 20 Year 2003 on National Education System part two of the Rights and Duties of Parents pursuant to Article 7 Paragraph (1) and Paragraph (2). Based on the theories of psychological need and the laws, parents and families have an obligation to provide the fulfillment of psychological needs for children.